Cytotoxicity evaluation of different clear aligner materials using MTT analysis - Ozkan Esra Cifci; Gok Gulay Dumanli; Ordueri Nazli Ece; Elgun Tugba (Sciendo, 2022)
Backround: The in vitro cytotoxic effects of six different clear aligner materials were evaluated using the MTT analysis.